Energy and valuable resource recovery from waste liquid crystal display panels by an environment-friendly technological process: Pyrolysis of liquid crystals and preparation of indium product. (20th September 2017) - Zhang, Lingen; Wu, Bi; Chen, Ya; Xu, Zhenming
Abstract: The contradiction of energy, resource and environment from waste liquid crystal display (LCD) panels is becoming more and more prominent because it contain both harmful liquid crystals and valuable metal indium. However, scarce researches have considered how to separate liquid crystals and recycle indium from waste LCD panels by an environment-friendly process. In this work, an integrated technological process to recycle energy and valuable resource from LCD panels is proposed. Firstly, a stripping product enriched liquid crystals and indium is gained by a mechanical stripping separation. Then, based on a series of pyrolysis separation, vacuum chlorinated separation and substitution reaction, concentration of indium is increased to 36 wt % in final product from 0.02 wt % in waste LCD panels. Several highlights were summarized as follows: (i) Feasibility, principle and reaction mechanism was studied to understand this integrated process. (ii) For pyrolysis process, separation rate of liquid crystals approached 82.06% under optimized parameters by response surface methodology. For vacuum chlorinated process, recovery rate of indium can reach 97.16%. This technological process is quite significant in accordance with the "Reduce, Reuse and Recycle Principle" for solid waste and further provides a new opportunity for sustainable development of LCD markets. Graphical abstract: Highlights: An integrated process is proposed to separate liquid crystals and recycle indium. Separation principles and reaction mechanism of integrated process are clarified. 82.06% liquid crystals and 97.16% indium was separated and recycled.